Estimación de parámetros genéticos de Gmelina arborea Roxb. (melina) en el Caribe de Costa Rica - Hernández-Castro, William; Badilla Valverde, Yorleny; Murillo-Gamboa, Olman (Uniciencia, 2021)
Gmelina arborea is one of the most important species in commercial reforestation projects in Costa Rica and is currently a significant part of the genetic improvement program led nationally by GENFORES. The objective of the present study is to determine the genetic parameters of 54 melina clones used in a clonal trial in the Caribbean region of Costa Rica. The trial was established in a randomized complete block design with four replications per treatment, with a distance of 4m x 3m. Genetic parameters were calculated at 10, 22, and 34 months, for the variables diameter at breast height (DBH), commercial height, commercial volume, and stem quality, using the SELEGEN REML/BLU software.  Genetic correlations were also made between the evaluated variables. Results indicated greater individual heritability in the broad sense for the commercial volume and DBH variables. In addition, the quality of the stem at 22 and 34 months presents the highest coefficients of individual heritability and the average heritability of the clone. The genetic correlations reflect high and positive values between the DBH-commercial volume-commercial height-stem quality variables, at 34 months of age, with 0.97 and 0.74, respectively. Clones 17 and 34 showed to be the best in the genetic ranking in terms of commercial volume, while the material control and clone 19 were last in the ranking. A 6.11% and 9.36% genetic gain was obtained at 34 months of age in DBH and commercial volume, respectively. It is concluded that there is genetic variability in the materials used, which allows us to obtain significant genetic gain, especially if using the first 10 clones of the genetic ranking.